Benchmarking of a checklist for the identification of familial risk for breast and ovarian cancers in a prospective cohort. Issue 3 (5th April 2019) - Rhiem, Kerstin; Bücker‐Nott, Hans‐Joachim; Hellmich, Martin; Fischer, Holger; Ataseven, Beyhan; Dittmer‐Grabowski, Christine; Latos, Kunibert; Pelzer, Volker; Seifert, Manuela; Schmidt, Andrea; Rezek, Daniela; Groh, Ulrich; et al.
Abstract: The detection of deleterious germline mutations in BRCA1 and BRCA2 considerably influences the clinical management of healthy and diseased carriers. Therefore, the identification of persons at risk who could uptake genetic counseling and testing is pivotal. We developed a checklist with validated criteria to improve the identification, and prospectively evaluate the incidence, of familial cancer history in 5091 breast cancer patients. The rate of 30.4% of patients at high genetic risk underpins the demand for care in risk identification and counseling. The easy‐to‐use instrument promotes the implementation and dissemination of risk counseling by physicians.